Large clonal expansions of CD8+ T cells in acute infectious mononucleosis. - Callan, M; Steven, N; Krausa, P; Wilson, J; Moss, P; Gillespie, G; Bell, J; Rickinson, AB; McMichael, A (1996)
Primary infection with Epstein-Barr virus often results in the clinical syndrome of acute infectious mononucleosis (glandular fever). This illness is characterized by a striking lymphocytosis, the nature of which has been controversial. We show that large monoclonal or oligoclonal populations of CD8+ T cells account for a significant proportion of the lymphocytosis and provide molecular evidence that these populations have been driven by antigen. The results suggest that the selective and massive expansion of a few dominant clones of CD8+ T cells is an important feature of the primary response to this virus.